Хятад хэлний хэлц үгийн бүтэц, онцлог, түүний заах аргын асуудалд: Structure and feature of Chinese phrases and its teaching methodology - Л., Солонго (Mongolian Studies, 2023)
In this article, the author has explained the peculiarities of Chinese phrases; its literal meaning, figurative meaning and metaphorical meaning which strongly connect to its national mentality. Chinese phrases reflect the history of China, its peoples’ lifestyle, culture, custom, economy and thinking. Teaching Chinese to Mongolian students, it is necessary to explain phrases from the point of etymology, lexicology, morphology and syntax base on the mentality of Mongolians and translating phrasal equivalents in Mongolian.